Organic Matter Controls of Iron Incorporation in Growing Sea Ice - Janssens, Julie; Meiners, Klaus M.; Townsend, Ashley T.; Lannuzel, Delphine (Frontiers in Earth Science, 2018)
This study presents the first laboratory-controlled sea-ice growth experiment conducted under trace metal clean conditions. The role played by organic matter, in the incorporation of iron (Fe) into sea ice was investigated by means of laboratory ice-growth experiments using a titanium cold-finger apparatus. Experiments were also conducted to understand the role of extracellular polymeric substances (EPS) in the enrichment of ammonium in sea ice. Sea ice was grown from several seawater solutions containing different quantities and qualities of particulate Fe (PFe), dissolved Fe (DFe) and organic matter. Sea ice and seawater were analyzed for particulate organic carbon and nitrogen, macro-nutrients, extracellular EPS, PFe and DFe, and particulate aluminium. The experiments showed that biogenic PFe is preferentially incorporated into sea ice compared to lithogenic PFe. Furthermore, sea ice grown from ultra-violet (UV) and non-UV treated seawaters exhibits contrasting incorporation rates of organic matter and Fe. Whereas the effects of UV-treatments were not always significant, we do find indications that the type or organic matter controls the enrichment of Fe in forming sea ice.. Specifically, we come to the conclusion that the incorporation of DFe is favored by the presence of organic ligands in the source solution.